2008
DOI: 10.4161/chan.2.1.5942
|View full text |Cite
|
Sign up to set email alerts
|

Stoichiometry of Kir channels with phosphatidylinositol bisphosphate

Abstract: Phosphatidylinositol bisphosphate (PIP 2 ) is the most abundant phosphoinositide in the plasma membrane of cells and its interaction with many ion channel proteins has proven to be a critical factor enabling ion channel gating. All members of the inwardly rectifying potassium (Kir) channel family depend on PIP 2 for their activity, displaying distinct affinities and stereospecificities of interaction with the phosphoinositide. Here, we explored the stoichiometry of Kir channels with PIP 2 . We first showed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
11
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 49 publications
4
11
1
Order By: Relevance
“…Identifiable contributions of ligand binding to individual subunits to overall activity have been noted in some other ligand-gated multisubunit channels. Thus, Harpsøe et al (2011) have recently described a biphasic ligand activation curve for ( α4 ) 3 ( β2 ) 2 nicotinic acetylcholine receptor channels (very like the present data) that results from binding to distinct high- and low-affinity sites; and, individual subunit contributions to homomeric Kir potassium channel open probability as a result of PI(4,5)P 2 binding to each of the four subunits have previously been deduced from the use of mutant subunits (Jin et al, 2008). Contributions to channel gating by ligand binding to less than the maximal number of subunits, resulting in partial channel openings to subconductance levels, have also been shown for AMPA (α-amino-3-hydroxy-5-methyl-4-isoxazolpropionate)-type homotetrameric glutamate receptors (Rosenmund et al, 1998) and heterotetrameric cyclic nucleotide–gated cation channels (Ruiz and Karpen, 1997).…”
Section: Discussionsupporting
confidence: 61%
“…Identifiable contributions of ligand binding to individual subunits to overall activity have been noted in some other ligand-gated multisubunit channels. Thus, Harpsøe et al (2011) have recently described a biphasic ligand activation curve for ( α4 ) 3 ( β2 ) 2 nicotinic acetylcholine receptor channels (very like the present data) that results from binding to distinct high- and low-affinity sites; and, individual subunit contributions to homomeric Kir potassium channel open probability as a result of PI(4,5)P 2 binding to each of the four subunits have previously been deduced from the use of mutant subunits (Jin et al, 2008). Contributions to channel gating by ligand binding to less than the maximal number of subunits, resulting in partial channel openings to subconductance levels, have also been shown for AMPA (α-amino-3-hydroxy-5-methyl-4-isoxazolpropionate)-type homotetrameric glutamate receptors (Rosenmund et al, 1998) and heterotetrameric cyclic nucleotide–gated cation channels (Ruiz and Karpen, 1997).…”
Section: Discussionsupporting
confidence: 61%
“…Kir channels stand out among channel subfamilies in that they have been studied extensively in terms of both their dependence on PIPs (Table 1) and their high-resolution structures (Table 2). Several studies on Kir channels have demonstrated direct effects of PIPs on single-channel gating (43, 54, 59, 60), strongly suggesting that channel-PIP interactions affect activity by altering protein conformation and gating. An alternative or parallel mechanism by which PIPs may alter activity is through regulating the number of channels by triggering their internalization from or insertion into the plasma membrane (see below).…”
Section: Phosphoinositide Control Of the Activity Of Ion Transport Prmentioning
confidence: 99%
“…Phosphorylation of Kir1.1 channels by PKA decreases the sensitivity to inhibition by PIP 2 antibodies, indicating an apparent increase in affinity for PIP 2 (Liou et al, 1999). Gβγ subunits of G-proteins and intracellular Na + alter PIP 2 sensitivity in Kir3.x channels (Huang et al, 1998; Zhang et al, 1999; Jin et al, 2008; Inanobe et al, 2010), while intracellular ATP decreases the apparent affinity of Kir6 channels for PIP 2 by reducing the channel's open probability (Baukrowitz et al, 1998; Shyng and Nichols, 1998; Enkvetchakul et al, 2000; Shyng et al, 2000; Wang et al, 2002b). …”
Section: Pip Regulation Of Kir Channelsmentioning
confidence: 99%
“…For most Kir channels, 1 or 2 open times and 1 or 2 closed times can readily be observed in single channel recordings depending on the specific isoform and recording conditions. With few exceptions (Fan and Makielski, 1997; Rohacs et al, 1999; Lopes et al, 2002), PIP 2 has generally been found to affect one or more of the closed times with no change in the open time(s) (Enkvetchakul et al, 2000; Jin et al, 2008; Xie et al, 2008; D'Avanzo et al, 2010a) suggesting a critical role for this lipid ligand in priming the channels for opening upon binding to a closed conformation. Several atomic resolution structures solved by x-ray crystallography (Nishida et al, 2007; Tao et al, 2009; Hansen et al, 2011; Whorton and MacKinnon, 2011, 2013) provide further support for this gating model.…”
Section: Pip Regulation Of Kir Channelsmentioning
confidence: 99%